Annuity as a Form of Compensation for Future Loss Caused by Torts - Szalma, József (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
This paper analyzes annuity, as a periodical obligation, which can emanate either from a contract, as in the case of maintainance or life annuity contract, or from tort. In the latter case, it has the function to provide compensation for future loss, but not in a single payment, which is regularly the consequence of liability for torts. The justification for such successive means of compensation is that by certain types of torts, such as in the case of disability or decreased ability to work, damage does not appear in one given moment, but accrues periodically, as successive future loss. An employee, for example, suffering personal injury, may become disabled to work or their ability to work may decrease, thereby they may earn less than previously. Damage in this case accrues each month in the amount of the difference between the wages earned before and after the injury. The author differentiates between successive annuity, as a rule, and cumulative annuity (lump sump), as an exception, justified by special considerations on the side of the injured, such as the need to bear the costs of professional retraining, for example. Regarding the determination of the amount of monthly annuity, the subject of analysis was the method of actuarial calculation, which takes into account both present damage and future loss. Due to the hypothetical nature of some elements of such determination, the law allows a subsequent revision of judgement on the amount of annuity, which has become conclusive, if the circumstances concerning the injured persons’s ability to work has changed substantially in the meantime. For instance, due to the subsequent deterioration of injured person’s ability to work, they may earn less or may not earn at all. Such subsequent revision of the judgement does not break through the rules on legal finality of judgements, since the effect of legal finality does not comprise new circumstances of the case. The author supports the standpoint that annuity is an adequate form of compensation for disability or decreased ability to work, since in such case the future loss accrues successively, in monthly differences of wages before and after the injury. Contrarily, by the overall decrease of viability, causing mental suffering due to impossibility of accomplishing former capabilities (such as the sense of sight, disability of movement), annuity is not a proper form of compensation, since immaterial damage does not emerge periodically, but in a single moment and lasts uninterruptedly.